Translation and cross-cultural adaptation of the European Health Literacy Survey Questionnaire, HLS-EU-Q16: the Icelandic version - Sonja Stelly Gustafsdottir; Arun K. Sigurdardottir; Solveig A. Arnadottir; Gudmundur T. Heimisson; Lena Mårtensson (BMC, 2020)
Abstract Background Health literacy (HL) is defined as the knowledge and competences of people to meet the complex demands of health in modern society. It is an important factor in ensuring positive health outcomes, yet Iceland is one of many countries with limited knowledge of HL and no valid HL measurement. The aim of this study was to translate the European Health Literacy Survey Questionnaire- short version (HLS-EU-Q16) into Icelandic, adapt the version, explore its psychometric properties and establish preliminary norms. Methods The HLS-EU-Q16 translation model included three steps: 1) translation-back-translation of HLS-EU-Q16 including specialists' review (n = 6); 2) cognitive interviewing of lay people (n = 17); and 3) psychometric analysis with survey participants. The HLS-EU-Q16 includes 16 items, with scores ranges from zero (low/no HL) to 16 (high HL). Statistics included were descriptive, internal consistency measured by Cronbach's α, exploratory factor analysis, and multivariate linear regression. Results After the translation and cognitive interviewing, 11 of the HLS-EU-Q16 items were reworded to adapt the instrument to Icelandic culture while maintaining their conceptual objectives. Survey participants were 251. Internal consistency of the translated and adapted instrument was α = .88. Four factors with eigenvalues > 1.0 explained 62.6% of variance. Principal component analysis with Oblimin rotation presented four latent constructs, "Processing and Using Information from the Doctor" (4 items, α = .77), "Processing and Using Information from the Family and Media" (4 items, α = .85), "Processing Information in Connection to Healthy Lifestyle" (5 items, α = .76), and "Finding Information about Health Problems/Illnesses" (3 items, α = .73). Lower self-rated health was an independent predictor of lower HL (β = −.484, p = .008). Preliminary norms for HL ranged from five to 16 (M 13.7, SD ± 2.6) with 72.5% with sufficient HL (score 13-16), 22% with problematic HL (score 9-12) and 5.5% with inadequate HL (score 0-8). Conclusions The Icelandic version of HLS-EU-Q16 is psychometrically sound, with reasonably clear factor structure, and comparable to the original model. This opens possibilities to study HL in Iceland and compare the results internationally. The translation model introduced might be helpful for other countries where information on HL is missing based on lack of validated tools.